Devir de um professor pelas veredas da Educomunicação: narrativa autoetnográfica - Camargo, André Luiz Rodrigues de (2018)
This paper aims to report and reflect on the transformation and unveiling of the teacher-researcher, in his daily professional and personal work. It privileges the two-year period devoted to the master’s in education of the PPGEdSo, bringing together the academic experiences and their intercurrences, as well as the processes of education by the mass media developed with students in the school space of ETEC de Piedade. The theoretical basis of this research to think the issues related to Communication and Educommunication are the writings of Paulo Freire, Mário Kaplún, Ismar de Oliveira Soares and Grácia Lopes Lima. The methodology of research is based on autoethnography, based on readings by Scribano and De Sena, Heewon Chang and Rodrigo Alberto Lopes. This process gathers the experiences of the masters and of the performance in the school ETEC de Piedade, within the project Biblioteca Ativa.